Cucurbit[6]uril p-xylylenediammonium diiodide decahydrate inclusion complex - Huang, Wei-Hao (International Union of Crystallography, 2008)
The title inclusion complex, C(36)H(36)N(24)O(12)·C(8)H(14)N(2) (2+)·2I(−)·10H(2)O, displays a large ellipsoidal deformation of the cucurbit[6]uril (CB[6]) skeleton upon complex formation. The benzene ring of the cation is rotationally disordered between two orientations in a ratio of 3:1. The solvent H(2)O molecules form a hydrogen-bonded network by interaction with the carbonyl groups of CB[6] and the I(−) counterions. The crystal studied exhibited non-merohedral twinning. Both CB[6] and the cation are centrosymmetric.